Profil Hasil Belajar Kognitif Siswa Dengan Metode Blended Learning Pada Materi Sistem Pernapasan Manusia: (Profile of Student Cognitive Learning Results With The Blended Learning Method in Human Respiratory System Materials) - Ellen Nurlindayani; Setiono Setiono; Suhendar Suhendar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Cognitive learning outcomes are the student's ability to understand a concept expressed in a score through a test. Cognitive learning outcomes are important learning outcomes as the basis for mastery of other abilities. The purpose of this study was to determine the cognitive learning outcomes of class XI IPA 2 students on the material of the human respiratory system. The research method used is a qualitative method using an instrument in the form of a multiple choice written test. The research was conducted on March 22, 2021. The subjects of this study were class XI IPA 2 with a total of 30 students. The data obtained is the result of students' cognitive learning on the material of the human respiratory system. The results obtained by an average value on the material of the human respiratory system are 27% of students in category A, 17% in category B, 30% with C criteria and 26% with D criteria. thus providing the achievement of better cognitive learning outcomes, the obstacle is the lack of direct interaction between educators and students. Abstrak. Hasil belajar kognitif merupakan kemampuan siswa dalam memahami suatu konsep yang di nyatakan dalam sebuah skor melalui tes. Hasil belajar kognitif merupakan hasil belajar yang penting sebagai dasar penguasaan kemampuan lainnya. Tujuan penelitian ini untuk mengetahui hasil belajar kognitif siswa kelas XI IPA 2 pada materi sistem pernapasan manusia. Metode penelitian yang digunakan metode kualitatif dengan menggunakan instrumen berupa tes tertulis pilihan ganda. Penelitian di lakukan pada 22 Maret 2021. Subjek penelitian ini adalah kelas XI IPA 2 dengan jumlah sebanyak 30 siswa. Data yang di peroleh merupakan hasil belajar kognitif siswa pada materi sistem pernapasan manusia. Hasil yang di peroleh rata-rata nilai pada materi sistem pernapasan manusia yaitu 27% peserta didik berkategori A, 17% berkategori B, 30% berkriteria C dan 26% berkriteria D. Penggunaan metode Blended learning membantu peserta didik dalam menambah pengetahuan yang lebih luas, namun kendalanya adalah kurangnya interaksi secara langsung antara pendidik dan peserta didik.